A new species of Pseudopyrochroa Pic, 1906 from Southwest China (Coleoptera: Pyrochroidae: Pyrochroinae) based on the last instar larva and adults, with natural history observations - Zhan, Zhihong; Jing, Kaixiang; Young, Daniel K. (Zootaxa, 2023)
A new species of the fire-colored beetle genus Pseudopyrochroa Pic, 1906, P. euryfoveata Zhan & Young, sp. n., is described and illustrated from Sichuan Province, Southwest China, based on the last larval instar (exuviae) as well as adult male and female specimens. Observations relating to the larval macro- and microhabitats and natural history notes are provided.